Investigating cognitive-enhancing supplement use among students at a Dutch life science university - Elena Escano; Nilüfer Sezer; Annemieke Maria Pustjens (PLoS ONE, 2025)
The use of cognitive enhancers among college students has drawn significant attention due to their impact on academic performance and health. This study investigates the prevalence, types, and motivations for cognitive-enhancing supplements (CES) use among students at Wageningen University & Research, as well as their perception of safety and authenticity aspects of CES. Data were collected from December 2023 to January 2024 via an online survey. The analysis was performed using R Statistical Language. Among the 288 students who participated (mean age = 23.1 years), 51.7% were aware of CES, with higher awareness among non-EU students (52.1%) compared to Dutch (20.5%) and other EU students (24.6%) (p = 0.001). Older students (40.5%) were more likely to consider using CES than younger ones (21.1%) (p = 0.005). CES usage was 11.5%, which is lower than in other European studies. Safety was a major concern, with participants trusting primarily scientific research but feeling inadequately informed about CES safety. Differences in authenticity concerns between users and non-users were noted (p = 0.003). The findings highlight the need for improved information and regulatory oversight regarding CES.